XX/XY sex chromosomes in a blind lizard (Dibamidae): Towards understanding the evolution of sex determination in squamates. (1st December 2022) - Rovatsos, Michail; Galoyan, Eduard; Spangenberg, Victor; Vassilieva, Anna; Kratochvíl, Lukáš
Abstract: The reconstruction of the evolutionary history of sex determination in squamate reptiles (lizards and snakes) is complicated by missing data in many lineages, erroneous reports, and often questionable inferences on state homology. Therefore, despite the large effort, the reconstruction of the ancestral sex determination in squamate reptiles is still controversial. With the hope to shed light on this problem, we aspired to identify the sex chromosome gene content in Dibamus deharvengi, the representative of the family Dibamidae, the putative sister clade to all other squamates. Our analyses revealed XX/XY sex‐determination system in D. deharvengi : the X chromosome contains genes with homologues scattered across chicken chromosomes 8, 12, 13, 18, 30, and 33, and the Y chromosome seems to largely degenerate. To the best of our knowledge, this combination has never been reported to form sex chromosomes in any amniote lineage. It suggests that the sex chromosomes can represent an apomorphy of a clade including D. deharvengi . Our findings cover an important gap in the knowledge of sex determination in reptiles and further support multiple independent origins of sex chromosomes in this group. Abstract : Comparative gene coverage analysis revealed XX/XY sex determination system in the blind lizard Dibamus deharvengi, the representative of a lineage of lizards with potentially basal phylogenetic position among squamate reptiles. The X chromosome contains genes with homologs scattered across chicken chromosomes 8, 12, 13, 18, 30 and 33, and the Y chromosome seems to be largely degenerated.